Management of gestational gigantomastia with breast reconstruction after mastectomy: case report and literature review. Issue 6 (June 2020) - Qin, Feng; Si, Loubin; Zhang, Hailin; Zhang, Mingzi; Zeng, Ang; Long, Fei; Yu, Nanze; Liu, Zhifei; Wang, Xiaojun
Gestational gigantomastia (GGM) is a rare complication of pregnancy. The etiology of GGM is yet to be fully established. Treatment methods for GGM include medical therapy and surgery. If medical treatment is unsuccessful, surgery may be required. Currently available surgical interventions are either breast reduction or mastectomy with delayed reconstruction. We report a case of a 25-year-old woman (G1P1) who presented with massive enlargement of both breasts during puerperium. Because of the limited effect of medical therapy, surgical intervention was considered to be the first choice. Bilateral mastectomies with grafting of the nipple–areola complex and immediate bilateral tissue expander implantation were performed. Reconstruction was fully completed 8 months after the initial procedure by replacing tissue expanders with definitive implants. Despite being a benign condition, GGM can turn into a serious problem. GGM can be successfully reconstructed by mastectomy with delayed reconstruction and grafting of the nipple–areola complex.